Key Practices Of Information Technology Governance Mechanisms For Public Sector: A Systematic Literature Review - Johan J.C. Tambotoh, Harjanto Prabowo, Sani Muhammad Isa, Bonifasius Wahyu Pudjianto (International Journal of Advanced Science and Technology, 2020)
IT-driven public sector innovation urges public sector to improve their IT Governance (ITG) capability through ITG mechanisms. The ITG mechanisms of the public sector are critical and important capabilities for decision makers to create public value through IT. In line with the increasing use of IT in the public sector, there have been increasing interests on ITG aspects in the public sector. However, the ITG mechanism in the public sector is still not well-defined yet in the sense that there are inconsistencies and misconceptions in determining ITG mechanisms in public organizations. Using systematic literature review (SLR) approach on 41 papers discussing ITG implementation and mechanisms in the public sector, this research found several key practices of ITG mechanisms based on decision-making structure, process or procedural and relational mechanisms.